India's potential as a lead market for frugal innovation and the role of socio-cultural context factors - Rajnish Tiwari (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2016)
In recent years a phenomenon called "frugal innovation" has increasingly gained traction in the scholarly discourse; and as research reveals, it is often brought in connection with India. Apparently, India has quietly acquired the role of a pioneer for innovations that aim at combining affordability with excellence, cutting across sectoral boundaries. But what is it that makes India a forerunner for an innovation paradigm with increasing global relevance? In this paper, I propose that the "lead market" theory can explain to a quite good extent the attractiveness of India for frugal solutions. On one hand, there are concrete economic factors that give rise to resource-efficient and affordable solutions to problems faced in day-to-day life. On the other hand, frugality has been long regarded as a virtuous social value in India and the socio-cultural context of the country provides a fertile environment for the acceptance of frugal products and services on both demand and supply sides. This paper, apart from dwelling on the concept of lead markets and its application in the context of frugal innovations in India, also presents some qualitative results of an empirical survey conducted with participation of Indian students that underscore the role of culture as a key determinant for the acceptance of frugal innovation. The study indicates that frugality in India is often driven by financial considerations ("frugality 2.0"), but globally there are other, additional powerful drivers for frugal innovations, e.g. environmental concerns and rejection of status symbols. This makes a case for collaboration and cooperation between emerging and developed economies, such as India, Germany and Japan, to enable "affordable green excellence".
Keywords: 330; Lead Markets; Frugality 3.0; Frugal Innovation; National Culture; India; Reverse Innovation